The return of the state: neocollectivism,agrarian politics and images of technological progress in the MAS era in Bolivia - Córdoba, Diana M.; Jansen, Kees (Wiley, 2014)
The Movement towards Socialism (MAS) party promised to break with neoliberal politics when it rose to power in Bolivia in 2006. Using the concept of neocollectivism to characterize MAS agrarian politics, this paper examines one of its key instruments for achieving rural development: the state enterprise EMAPA. This state company, which supports small producers, envisions a new agrarian structure of production and commercialization, one that will break the power of the Santa Cruz–based agro‐industrial elite. Drawing on a discussion of the mechanisms of governance employed by this state entity, we argue that new complexities in state–civil society relations and a low state capacity have constrained its ability to shift power relationships between the state and the agro‐industrial elites. Instead of reducing the dependency of small producers on agro‐industrial capital, the Bolivian state has increased it, thereby undermining its goal of redistribution. The paper also analyses different moments of politicization and depoliticization in the intervention process arising from the demand for political change, as well as for technically efficient and profitable agricultural production.